Third Parties, War Systems' Inertia, and Conflict Termination:: The Doomed Peace Process in Colombia, 1998-2002 - Richani, Nazih (Journal of Conflict Studies)

(untitled) (The University of New Brunswick, 2005)
ABSTRACT This article discusses the role of third-party interventions in the failed peace process of Colombia that took place between 1998 and 2002. It analyses how both neutral and biased interventions impacted upon conflict dynamics. The article demonstrates that the neutral intervention was limited to the initiation of the peace talks and intermittent particularly in its final phase, while the biased intervention, led by the US, changed the incentive structure of the actors involved, creating hopes among the hard liners that the US could help them in winning the war. In hindsight, this biased intervention failed to tip the balance of power, but contributed to the derailment of the peace process. This article argues that third party intervention, particularly the biased intervention, failed to dismantle the war system. Instead, it has brought the Colombian war system into a phase of fluctuating stalemate, characterized by renewed volatility and violence.